Review of the tribe Mutillini (Hymenoptera: Mutillidae) from the Oriental Region - Lelej, Arkady S.; Williams, Kevin A.; Terine, Joshua B.; Okayasu, Juriya; Parikh, Grishma R.; Kumar, Girish P. (Zootaxa, 2023)
The species in the tribe Mutillini (Mutillidae: Mutillinae) sensu Waldren et al. (2022, in press) of the Oriental region are reviewed. Fourteen species in the genera Kurzenkotilla Lelej, 2005, Mutilla Linnaeus, 1758, Standfussidia Lelej, 2005, and Storozhenkotilla Lelej, 2005 are keyed, reviewed, and illustrated. The males of the genus Kurzenkotilla are described and associated with the females. One new species: Storozhenkotilla nathani Lelej, sp. nov., male is described from India (Karnataka and Kerala). New combinations are proposed for Kurzenkotilla harmandi (André, 1898), comb. nov., K. rufodorsata (Cameron, 1897), comb. nov., K. semiviolacea (André, 1896), comb. nov., K. cicatricifera (André, 1894), comb. nov., and Storozhenkotilla binghami (Lelej, 2005), comb. nov. Six new country records are presented: Kurzenkotilla niveosignata (André, 1894) from Pakistan, K. annamensis Lelej, 2005 from Thailand, K. visrara (Cameron, 1898) from India, K. scrobiculata (Hammer, 1962) from Nepal, K. rufodorsata (Cameron, 1897) from Nepal, and Storozhenkotilla binghami Lelej, 2005 from Sri Lanka. Specimens of Mutilla mikado Cameron, 1900 from China were misidentified as Mutilla europaea by Su et al. (2019), and we recognize M. mikado as the sole member of the genus Mutilla to occur in the Oriental region. A key to the species of Oriental Mutillini is provided.